ANALISIS PERBEDAAN INDEKS PRESTASI KUMULATIF MAHASISWA PENDIDIKAN MATEMATIKA BERDASARKAN TIPE KEPRIBADIAN EKSTROVERT DAN INTROVERT - Yana Tasya Damanik; Irvan Irvan; Johannes Gultom (Universitas Islam Sumatera Utara, 2025)
This research is a quantitative research employing an ex post facto approach aimed at examining the differences in Grade Point Average (GPA) of mathematics education students based on extrovert and introvert personality types. Data collection was conducted online using a validated personality questionnaire consisting of 20 items, distributed via the Google Form platform. The research sample comprised 28 students, including 14 extroverted and 14 introverted individuals. Data analysis involved a normality test using the Kolmogorov-Smirnov test and a hypothesis test using the Independent Samples t-test. The results showed that there was no significant difference in the GPA of mathematics education students between extrovert and introvert personality types. Therefore, personality type does not significantly influence students' academic achievement in terms of GPA within this context.